2021
DOI: 10.33546/bnj.1670
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between knowledge and self-efficacy of nurses regarding early initiation of cardiopulmonary resuscitation and automated defibrillation in Saudi Arabia

Abstract: Background: Cardiopulmonary resuscitation (CPR) and early defibrillation are the most common procedures performed by nurses as the first responders to cardiac arrest patients in the hospital setting. Therefore, nurses are demanded to have high skills for effective performance. Self-efficacy and knowledge are considered significant factors affecting early initiation of CPR and automated defibrillation. However, previous studies mostly focused on nursing students instead of frontline nurses. Objective: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Demirtas et al 26 also found that nurses’ knowledge and abilities increased due to simulation-based CPR instruction. Alaryani et al 27 found that 63.8% had high self-efficacy (44.627%±58.397%). The highest domain of self-efficacy was responding and rescuing, while the lowest was debriefing and recording.…”
Section: Discussionmentioning
confidence: 98%
“…Demirtas et al 26 also found that nurses’ knowledge and abilities increased due to simulation-based CPR instruction. Alaryani et al 27 found that 63.8% had high self-efficacy (44.627%±58.397%). The highest domain of self-efficacy was responding and rescuing, while the lowest was debriefing and recording.…”
Section: Discussionmentioning
confidence: 98%
“…Job performance and student learning can be predicted by self-efficacy levels (Lowe et al, 2022). Research by Alaryani et al (2021) demonstrated that a positive relationship existed between high levels of knowledge and high levels of self-efficacy. Thus, while the findings of Research question one were not statistically significant, the enhanced learning lab of fabricating orthotics in this study may be instructionally significant.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…13 Self-efficacy sendiri meningkat apabila ditunjang dengan pengetahuan yang tinggi. 14 Dengan demikian dapat dijelaskan bahwa faktor yang paling berperan dalam membentuk self-efficacy penderita adalah pengetahuan yang dimiliki oleh penderita itu sendiri, lebih lanjut dapat disimpulkan bahwa pengetahuan mempunyai peran penting dalam praktik kepatuhan seseorang. 15 Penelitian terdahulu mengenai topik yang serupa dengan penelitian ini telah banyak dilakukan dan juga telah banyak dipublikasikan.…”
Section: Pendahuluanunclassified